Sosialisasi Prosedur Pembiayaan Gadai Emas Pada PT. Bank Syariah Indonesia KCP Radial Kota Palembang - Adzin Syarif; Agung Anggoro Seto (CV. IRA PUBLISHING, 2023)
Pawning gold is a financing instrument that can be used by people who need fast and easy financing. However, to obtain gold pawning financing, there are procedures and requirements that must be met by customers or the public. The public's lack of knowledge regarding the procedures and requirements for gold pawning financing is allegedly the cause of the suboptimal marketing of gold pawning at PT. Indonesian Sharia Bank KCP Radial Palembang. This community service activity aims to socialize gold pawning financing procedures at Bank Syariah Indonesia KCP Palembang Radial. This activity is important as a means of marketing gold pawn financing products as well as providing understanding to the public about financing products that can be used as alternatives when they need funds. The design of this service activity consists of several stages, such as identifying problems related to gold pawning procedures and marketing, socializing the requirements for applying for gold pawning financing, analyzing and socializing the assessment process for gold pawning financing and contract procedures for gold pawning financing agreements. The results of this service activity concluded that the gold pawn product is one of the financing products that has the potential to become a product that is liked by the public/customers in line with customer needs for easy, fast and safe financing products. To carry out the gold pawning financing process requires established requirements and procedures. Implementing gold pawning requires additional outreach and promotion by BSI Bank.